2018
DOI: 10.1093/jee/tox357
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Inspection Efficacy by Member States of Wood Packaging Material Entering the European Union

Abstract: The use of wood packaging materials (WPMs) in international trade is recognized as a pathway for the movement of invasive pests and as the origin of most introductions of Asian longhorned beetle, Anoplophora glabripennis (Motschulsky) (Coleoptera: Cerambycidae) in Europe and North America. Following several pest interceptions on WPM associated with stone imports from China, the European Union (EU) agreed to survey certain categories of imports based on the EU Combined Nomenclature Codes for imports, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
0
12
0
2
Order By: Relevance
“…Overall trends in ant interceptions did not increase along with trends of transport / trade into Australia through the same time period. This pattern suggests that either the number of ants being transported per voyage has changed, decreasing from 2004-2010, or that the proportion of ant transport events that are detected has changed (e.g., Eyre et al 2018). There is some evidence for the latter; due to occurrence overseas of Bovine spongiform encephalopathy, there was an increase in biosecurity effort in 2000-2002 such that 100% of imported containers were checked externally (Adam Broadley pers.…”
Section: Discussionmentioning
confidence: 99%
“…Overall trends in ant interceptions did not increase along with trends of transport / trade into Australia through the same time period. This pattern suggests that either the number of ants being transported per voyage has changed, decreasing from 2004-2010, or that the proportion of ant transport events that are detected has changed (e.g., Eyre et al 2018). There is some evidence for the latter; due to occurrence overseas of Bovine spongiform encephalopathy, there was an increase in biosecurity effort in 2000-2002 such that 100% of imported containers were checked externally (Adam Broadley pers.…”
Section: Discussionmentioning
confidence: 99%
“…Eyre and colleagues (2018) observed that the highest detection rates were achieved in Austria and France, whereas in Spain and Poland, despite the inspection of more than 500 consignments, no harmful organisms were detected. The authors suggested that harmonizing the inspection procedures to the most effective methodology may lead to an approximate sevenfold increase in the number of interceptions of invasive pests across all member states (Eyre et al 2018). A study on relationships between interceptions and establishments of Cerambycidae (including ALB and CLB) found that there is a significant positive relationship overall between these parameters (Brockerhoff et al 2014), which highlights the potential usefulness of recording interception data from inspections of relevant imports.…”
Section: Interceptionsmentioning
confidence: 99%
“…There have been strong global efforts in recent years to reduce the risk of international movement of plant pests by the pathways discussed here. The International Plant Protection Convention (IPPC) is the main organization that sets global standards for plant health (Allen et al 2017 (Eyre et al 2018;Wu et al 2017). Such interceptions could indicate issues such as ineffective treatment standards, faulty equipment, or fraud (Haack et al 2014).…”
Section: Policy and Managementmentioning
confidence: 99%
“…Such interceptions could indicate issues such as ineffective treatment standards, faulty equipment, or fraud (Haack et al 2014). Interception records of insects associated with WPM also vary among countries, likely reflecting differences in trading partners and inspection protocols (Eyre et al 2018). For example, the USA historically placed more emphasis on insects that infest living trees rather than dead trees or processed wood, which resulted in inspectors reporting true bark beetles (which often infest live trees) more often than ambrosia beetles, Anobiidae and Bostrichidae (which often infest dead trees or lumber) (Haack 2001(Haack , 2006.…”
Section: Policy and Managementmentioning
confidence: 99%